Analisis Model Pembelajaran Konvesional dan Model Pembelajaran Islam - Huda, Samsul; Rusdiono; Hasanah, Tita; Lestari, Hana; Rusydi, Lina Najwatur (JURNAL KAJIAN ISLAM MODERN, 2024)
This research aims to determine the comparison between conventional learning models and Islamic learning models. This research uses library research methods, and data collection uses documentation methods. The data analysis uses comparative techniques, namely analyzing the philosophical foundations of conventional learning and Islamic learning and looking at these two learning concepts from the perspective of Islamic education. The research results show that Islamic education has a very comprehensive range of learning models with efforts to help develop students to be more independent based on good values ​​in their lives, so that they can form individuals who have good morals in relation to life. reason, feeling and action. The two learning models are very different conceptually, so there is a need for creative collaborative efforts from a teacher as a mediator and catalyst in the learning process. Therefore, these two learning models can be more useful according to conditions and situations, so that between conventional learning models and Islamic learning models creative and innovative collaboration will be created. In fact, learning with this model is very suitable for current comprehensive education needs Keywords: Model, Learning, Education, Islam